An Analysis of the Job Creation Law and Efforts to Strengthen National Economic Resilience in the Face of a Potential Global Recession: A Study on the Development of a Biomass Power Plant (Wood Chip Co-Firing) - Kusbianto; Dody Syafnul; Ahmad Braja Wahyu; Arie Satria; Ali Bakti (PT FORMOSA CENDEKIA GLOBAL, 2026)
The threat of a global recession due to the global economic slowdown, rising energy prices, and geopolitical instability has prompted Indonesia to strengthen its economic resilience through energy diversification. One alternative being developed is wood-chip-based biomass as a co-firing fuel in coal-fired power plants to reduce dependence on coal. This study aims to analyze the role of Law No. 11 of 2020 on Job Creation in accelerating the development of biomass-fired power plants and its contribution to national economic resilience. The research method used is normative legal analysis with a legislative and conceptual approach. The results of the study indicate that the Job Creation Law accelerates biomass development through risk-based licensing reforms, simplified environmental approvals, and streamlined forestry permits, thereby enhancing legal certainty for renewable energy investments. These policies also support the acceleration of the biomass supply chain and the implementation of co-firing programs in coal-fired power plants. However, their implementation still faces technical challenges, infrastructure limitations, and the need for policy harmonization across sectors. This study concludes that wood-chip-based biomass power plants have the potential to serve as a strategic instrument in strengthening energy security and national economic stability amid the threat of a global recession.